The Impact of Multidisciplinary Team Meetings on the Survival of Stage IV NSCLC Patients - Zhengyang Lu; Nan Zhang; Qian Gao; Pengfei Li; Weimin Guan; Shihong Lin; Wenxuan Yan; Boyu Liu; Youhua Lu; Jinming Yu (Cancer Medicine, 2025)
ABSTRACT Background With treatment strategies for cancer constantly evolving, the multidisciplinary team (MDT) plays a key role in optimizing cancer care, but its real‐world impact on survival remains unclear. This study aims to examine the impact of MDT on overall survival (OS) among patients with stage IV non‐small cell lung cancer (NSCLC), based on real‐world data including all eligible patients. Method Patients with stage IV NSCLC who were admitted for the first time to Shandong Cancer Hospital from January 1, 2021 to December 31, 2021 were divided into MDT group and non‐MDT group according to MDT meeting involvement. Follow‐up period extended from January 1, 2021, to May 31, 2024. Kaplan–Meier curves and log‐rank tests were used to analyze survival differences, while Cox proportional hazards models were employed to identify factors associated with overall survival. Result One thousand six hundred and sixty‐four patients were included. No statistical differences were found between the MDT group (n = 1238) and the Non‐MDT group (n = 426) in baseline characteristics, but differences were observed in treatment modalities. The MDT group exhibited a longer median overall survival compared to the Non‐MDT group (26.25 vs. 21.42 months; log‐rank χ2  = 4.93, p = 0.03). Furthermore, MDT was associated with a reduction in the risk of mortality (adjusted HR = 0.86; 95% CI, 0.75–0.99; p < 0.05). Conclusion MDT can effectively reduce mortality risk. Future implementation requires recognizing its potential additional benefits and developing tailored strategies.